Synthesis, Characterization and Pharmacological Activities of 3,6-Disubstituted-1,2,4-triazolo [3,4-b]-1,3,4-thiadiazoles and their Dihydro Analogues - Vinod Mathew; J. Keshavayya; V. P. Vaidya (E-Journal of Chemistry)
4-Amino-5-aryl/heteroaryl substituted-3-mercapto-1,2,4-triazoles 3(a-d) were prepared from the corresponding aromatic carboxylic acids through a multi-step sequence. Compounds 3(a-d) were made to react with various aromatic/hetero aromatic acids and hetero aromatic aldehydes to give 3,6-disubstituted-1,2,4-triazolo [3,4-b]-1,3,4-thiadizoles and 3,6-disubstituted-5,6-dihydro-1,2,4-triazolo [3,4-b]-1,3,4-thiadizoles respectively. Elemental analysis, IR, 1H NMR and mass spectral data elucidated the structures of all newly synthesized compounds. Synthesized compounds are studied for their antibacterial, antifungal, anti-inflammatory and analgesic activities. Some of the tested compounds showed significant pharmacological activities.